2007
DOI: 10.1016/s1472-6483(10)61042-5
|View full text |Cite
|
Sign up to set email alerts
|

New alternative to infertility treatment for women without ovarian stimulation

Abstract: Natural cycle IVF produced the world first successful live birth, but slowly this treatment has been replaced by ovarian stimulated cycle IVF, because it has been believed ovarian stimulated cycle IVF will increase the number of available embryos for transfer. Therefore, it directly increases the chance of pregnancy from the treatment cycle. However, ovarian stimulation is always associated with side effects. The recovery of immature oocytes followed by in-vitro maturation (IVM) and IVF is an attractive altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 31 publications
2
32
0
4
Order By: Relevance
“…In this study, surprisingly, we have discovered that some mature oocytes can be retrieved from relatively small follicles (between 8 to 10 mm in diameter). We have demonstrated that the embryo development from in vivo matured oocytes had better quality than in vitro matured oocytes, resulting in a higher clinical pregnancy rate in the natural cycle IVF/M treatment with in vivo matured oocytes compared to the cycles without in vivo matured oocytes [Lim et al 2007b]. It has also been reported that in vivo matured oocytes from polycystic ovary syndrome (PCOS) infertile women had significantly higher clinical pregnancy rates compared to patients without in vivo matured oocytes retrieved [Son et al 2008].…”
Section: Discussionmentioning
confidence: 97%
“…In this study, surprisingly, we have discovered that some mature oocytes can be retrieved from relatively small follicles (between 8 to 10 mm in diameter). We have demonstrated that the embryo development from in vivo matured oocytes had better quality than in vitro matured oocytes, resulting in a higher clinical pregnancy rate in the natural cycle IVF/M treatment with in vivo matured oocytes compared to the cycles without in vivo matured oocytes [Lim et al 2007b]. It has also been reported that in vivo matured oocytes from polycystic ovary syndrome (PCOS) infertile women had significantly higher clinical pregnancy rates compared to patients without in vivo matured oocytes retrieved [Son et al 2008].…”
Section: Discussionmentioning
confidence: 97%
“…Natural-cycle in vitro fertilization (IVF) combined with in vitro maturation (IVM) of immature oocytes (natural-cycle IVF/M) has become a novel treatment for infertile populations and has been looked on with increasing interest (1)(2)(3). Compared with stimulated-ovary IVF cycles, the advantages of natural-cycle IVF/M are simpler and cheaper.…”
mentioning
confidence: 99%
“…Chian et al (8) observed that the developmental competence of bovine oocytes from small follicles is not affected either by the presence of a dominant follicle or by the phase of folliculogenesis. Following this, the combination of natural-cycle IVF with IVM has successfully resulted in pregnancy for infertility (1)(2)(3).…”
mentioning
confidence: 99%
“…The serum hormone levels were measured by using an enzyme immunoassay (AIA-1800, TOSO, Tokyo, Japan). In patients who had a dominant follicle ≥ approximately 17 to 18 mm [1], LH surge was not observed or initiated (LH≥20 mIU/ml or LH levels/LH basal levels >1.5 [4]), GnRH agonist was administered to induce endogeneous LH surge [2]. In case, E 2 levels was lower than previous data and P 4 levels was higher, or LH levels was going to decrease, we considered that the LH surge was triggered spontaneously [5].…”
Section: Methodsmentioning
confidence: 99%
“…Soon thereafter, natural IVF was replaced by stimulated IVF because of the very high cancellation rate of natural cycles, and stimulated treatment became the standard in IVF [2]. The side effects of ovarian stimulation with gonadotropins, including ovarian hyperstimulation syndrome (OHSS), have been well described.…”
Section: Introductionmentioning
confidence: 99%